ENHANCING LEARNING: EFFECTIVE STRATEGIES FOR TEACHING CHILDREN (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This topic is about most effective way of teaching children. How they can communicate to each other without embarrassment, how they can speak fluently and clearly. What is the best way to teach them? You can take answer to all your question.